The effect of hypocapnia on systemic perfusion in patients with single ventricle after surgery - A. В. Naumov; G. G. Khubulava; Yu. S. Аleksandrovich; S. P. Marchenko; К. V. Pshenisnov; N. G. Pilyugov (Вестник анестезиологии и реаниматологии, 2021)
The objective: the aim of the study was to identify the relationship between arterial hypocapnia and systemic hypoperfusion in newborns with single ventricular physiology after hemodynamic correction of congenital heart disease. Subjects and methods. 125 newborns with congenital heart defects operated from 2014 to 2018 were examined retrospectively.  Arterial and central venous blood gases were collected in the postoperative period.  A total of 670 pairs of laboratory results were selected.Results. Based on the presence/absence of hypocapnia (PaCO2 less than 35 mm Hg), 2 groups were formed. Group G-0 (the hypocapnic variant of the single-ventricular circulation) comprised 44 observations. Group G-1 (PaCO2 more than 35 mm Hg) included 40 observations.  In 32 (38%) cases the level of systemic perfusion was within the normal range, in 52 (62%) cases, systemic hypoperfusion was detected.  In samples corresponding to Group G-1, signs of DOS were observed in 20 cases.  The study showed that the most pronounced intergroup difference in parametric data was observed among indicators reflecting oxygen consumption and, as a consequence, the system flow rate (РO2 in mixed venous blood, saturation in mixed venous blood, arterio-venous difference in saturation, O2 content in venous blood, O2 extraction ratio, arterio-venous difference in РCO2).  In addition, the HF markers such as arterio-venous difference in saturation, O2 extraction ratio, arterio-venous difference in РCO2 had a strong correlation with the signs of systemic hypoperfusion. In the hypocapnic group, the tendency for more pronounced desaturation of venous blood was determined, and a higher arterio-venous difference in saturation, O2 content in venous blood, O2 extraction ratio, and arterio-venous difference in РCO2 parameters were also noted.Conclusions. Arterial hypocapnia may be a sign of pulmonary overflow and reduction of systemic blood flow in newborns with single ventricular physiology, after hemodynamic correction of congenital heart disease.  When managing newborns with parallel circulation, hypocapnia should be avoided as a factor contributing to the redistribution of blood flow from left to right and the development of systemic hypoperfusion.